Magnetic resonance imaging for characterization of hepatocellular carcinoma metabolism - Wang, Lixia; Yang, Ju Dong; Yoo, Charles C.; Lai, Keane K. Y.; Braun, Jonathan; McGovern, Dermot P. B.; Xie, Yibin; Pandol, Stephen J.; Lu, Shelly C.; Li, Debiao (Frontiers in Physiology, 2022)
With better understanding of the pathophysiological and metabolic changes of hepatocellular carcinoma (HCC), multiparametric and novel functional magnetic resonance (MR) techniques, and positron emission tomography/MR (PET/MR) have gained wide interest and increasing applications in preclinical and clinical research. These techniques not only allow for non-invasive detection of structural, functional, and metabolic changes of malignant tumor cells, but also reflect the characteristics of the tumor microenvironment (TME) and the interactions of malignant tumoral cells with TME. The characteristics of TME are hypoxia, low pH, which results from the Warburg effect, and many metabolites produced by tumor cells and other cellular components. The heterogeneity and complexity of TME require that more imaging parameters and modalities be combined to qualify and quantify individual tumors, further helping to identify suitable therapy. This review focuses on the value of multiparametric MRI and PET/MR in reflecting the structures and functional changes of HCC, detecting metabolites caused by HCC and the TME.